[Rezension von: Lucilla Guidi, Thomas Rentsch (Eds.), Phenomenology as performative exercise] - Arnold, Thomas (Phenomenological Reviews, 2020)
This volume, edited by Lucilla Guidi and Thomas Rentsch, establishes the first systematic connection between phenomenology and performativity.
Gesehen am 16.10.2020
Keywords: Rezension